2020
DOI: 10.3390/genes11101125
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Analysis of the Pentatricopeptide Repeat (PPR) Gene Family and PPR-Derived Markers for Flesh Color in Watermelon (Citrullus lanatus)

Abstract: Watermelon (Citrullus lanatus) is an economically important fruit crop grown for consumption of its large edible fruit flesh. Pentatricopeptide-repeat (PPR) encoding genes, one of the large gene families in plants, are important RNA-binding proteins involved in the regulation of plant growth and development by influencing the expression of organellar mRNA transcripts. However, systematic information regarding the PPR gene family in watermelon remains largely unknown. In this comprehensive study, we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Matsum. & Nakai), ClaPPR140 cosegregates perfectly with red flesh colour [ 48 ]. In woodland strawberry ( Fragaria vesca L.) accessions with white fruits, PPRs are among the genes significantly downregulated, compared with accessions with red fruits [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Matsum. & Nakai), ClaPPR140 cosegregates perfectly with red flesh colour [ 48 ]. In woodland strawberry ( Fragaria vesca L.) accessions with white fruits, PPRs are among the genes significantly downregulated, compared with accessions with red fruits [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the MADS-box transcription factor (TF) RIPENING INHIBITOR (RIN), STAY-GREEN 1 (SGR1), AP2/ethylene response factor-type TF (RAP2.2), and phytochrome interacting factor 1 (PIF1) regulate the accumulation of carotenoids in tomato fruits by interacting with the SlPSY1 promoter . In watermelon, four PPR family genes, which are important RNAbinding proteins in plants, were correlated with flesh color (Subburaj et al, 2020). In the present study, several transcriptional regulators were identified in the candidate region for Clwf2, such as the PPR protein (Cla97C06G121830), the TPR protein (Cla97C06G121890), and AP2/ERF (Cla97C06G121910) (Supplementary Table S5).…”
Section: Discussionmentioning
confidence: 62%
“…In Arabidopsis, ARR4 transcription factor acts as a signaling module in the light signal transduction pathway (Haberer and Kieber, 2002). A study using GBSbased BSA-seq analysis in pepper identified a candidate gene CaPRR2 related to plastid development and pigment biosynthesis, affecting the levels of chlorophyll a and chlorophyll b and controlling the color of fruit (Lee et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that genotyping 70 lines utilizing four SNPs from four ClaPPRs resulted in match rates above 0.87 for each validated SNP in association with the distinct phenotypes of skin colour. These findings contribute to a better knowledge of PPR genes and their functions in watermelon fruit growth and ripening, which may be useful in watermelon cultivar improvement (Subburaj et al, 2020). GhImA, which encodes a PPR protein, is involved in mitochondrial nad7 splicing, respiratory metabolism, and cotton fibre formation via ATP supply and ROS balancing (Zhang et al, 2021).…”
Section: Pprs Participate In Stress Responsesmentioning
confidence: 78%